Literature Study on the Effectiveness of PPnBM and PPh Article 22 Collection in Increasing State Revenue - Amanda Putri Aisyah; Alfan Prihandiki; Bela Amanda Putri; M. Irvan Tanjung; Zaskia Zahira; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
Taxes are one of the main sources of state revenue that are crucial for financing development and the needs of society, such as infrastructure, education, and other public services. Among the various types of taxes available, VAT on Luxury Goods (PPnBM) and Article 22 Income Tax (PPh Pasal 22) play a unique role as they are applied selectively and target specific activities, such as the purchase of luxury goods or import activities. This study is conducted using a literature method, by collecting and analyzing data from various sources such as journals, government documents, and legislation. The results show that PPnBM and PPh Pasal 22 contribute significantly to state revenue. However, in practice, there are still many challenges such as complex regulations, lack of public knowledge, and low tax compliance. Therefore, more friendly strategies are needed, such as easily understandable socializations, simpler administrative systems, and the utilization of technology so that the public becomes more compliant and the tax collection process becomes more efficient. If this can be realized, taxes can truly function as an important tool to achieve fair and equitable development